TINJAUAN YURIDIS TINDAK PIDANA TERORISME DI INDONESIA - Agus Suparmono (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT One of the things that disturb national stability is the crime of terrorism. In recent years, criminal acts of terrorism in Indonesia have mushroomed and have disturbed the peace of the nation. The series of bombings that occurred in the territory of the Unitary State of the Republic of Indonesia has caused widespread fear in the community, resulting in loss of life and loss of property, thus causing an unfavorable influence on Indonesia's social, economic, political, and international relations. Bombing is one mode of perpetrators of terrorism that has become a common phenomenon in several countries. Terrorism is a transnational, organized crime and even an international crime that has a wide network, which threatens national and international peace and security.Problem approach is the process of solving or solving problems through the stages that have been determined, so as to achieve research objectives. In this type of approach, researchers make direct observations of the process of enactment of normative law in certain legal events so that this study examines the legal provisionsThe elements in the criminal act of financing terrorism, namely every person, who commits an evil conspiracy, attempted or assisted to commit the crime of financing terrorism, intentionally providing, collecting, giving, or lending funds either directly or indirectly, with the intention of being used in whole or in part to commit acts of terrorism, terrorist organizations, or terrorists.From the point of view of law enforcement officers, it turns out that the AT Special Police Detachment 88 personnel in charge of investigating and investigating terrorist crimes committed by radical groups because members of the Special Detachment 88 AT Polri who are already trained and experienced in their duties, so that the disclosure of the case does not encounter obstacles or significant obstacles, and from the results of an investigation conducted immediately the suspect can be arrested to carry out his investigation. Keywords: Criminal Acts, Terrorism, Law Enforcement